Experiences of trans women who have undergone gender affirmation surgery: a constructivist grounded theory - Dharsheni, S. T. S.; Sivakami, B. (Frontiers in Sociology, 2025)
IntroductionGender Affirmation Surgery often referred to as ‘Nirvana’ in the transgender community in India is a major process that most trans women undergo. It is practiced in the traditional way as, the thayamma operation (midwife procedure) where the elderly transwoman cut off the penis and testicles without any anesthesia or medical supervision. However, the medical procedure of GAS in India is a recent advancement, which is accessible only to a few, the procedure that most trans women have undergone is penectomy (removal of the penis) and orchiectomy (removal of the testicles).AimThis study aims to explore the experiences of trans women who have undergone gender-affirmation surgery (GAS) during the period 2005–2023 in Chennai, India.MethodIn academia, research papers discuss the medical aspects of gender affirmation surgery but the experiences of the individuals undergoing this surgery remain under-researched and under-documented, which was the main reason to apply a constructivist grounded theory approach. Seventeen trans women from various non-governmental organizations (NGOs) in Chennai, India participated in the in-depth interviews, which were conducted in two sessions, to gain insights into their lived experience of undergoing gender affirmation surgery.ResultThis study, using initial coding, focused coding, and theoretical coding, reveals both the positive and negative aspects of the surgery experiences of trans women using the five focused codes: decision to undergo surgery, support systems, healthcare experiences, postoperative outcomes, and impact on identity and well-being.DiscussionThe study highlights the resilient nature of trans women in India, who despite facing adversity, become advocates for better healthcare and social understanding. The findings emphasize the importance of inclusive policies and practices that address the unique needs of trans women.